τ-Group Congruences on E-Inversive τ-Semigroups: Supavinee Sattayaporn - Team, Support (Thai Journal of Mathematics, 2009)
In this paper, we give a characterization and some properties of E-inversive τ-semigroup. Moveover, we also introduce a τ-group congruence on any E-inversive τ-semigroup and give its characterizations. Our main results improve and extend many results obtained by Seth [1].